Statistical Sampling Techniques in the Aging of Accounts Receivable in a Department Store - Cyert, R. M.; Trueblood, Robert M. (Management Science, 1957)
In the economic systems of most industrial countries the bulk of the sales made by business concerns of any significant size is in the form of credit sales. In large retail outlets such as department stores, credit sales become even more important and the number of accounts receivable becomes exceedingly large. Under such conditions the proper credit policy to be followed becomes a management problem of the first magnitude. In addition to the proper credit policy it is necessary for management to determine the proper reserve for uncollectibles. One of the traditional methods of generating information on these questions has been the aging of the accounts receivable. It is precisely on management problems of this kind, where good information about large masses of data must be derived, that modern statistical sampling techniques can play an important role. When the data for decision-making purposes are the result of a statistical sample, management has an objective measure of the quality of the data on which the decision may be made. The specific objective of this paper is to demonstrate the usefulness of statistical sampling in the aging of receivables for the purpose of setting the allowance for uncollectibles.